Avaliação do desprendimento do fruto do cafeeiro por vibração: um estudo de caso - Gomes, Jader Bôsco (2017)
The cherry phase of the coffee is the most widely used for marketing and its harvest is carried out in several ways, the most common being manual, semi-mechanized and mechanized. In order to contribute to the efficiency of this process, this work aims to evaluate, in a semi-mechanized harvesting system, in which a vibrator is attached to the coffee plant branch,what frequency of the vibration is responsible for taking the largest amount of fruit of that stage. In this regard, several funding instruments have been tested and the electret microphone was the best adapted to the conditions of branches and fruits of plants installed in the laboratory of the Center of Instrumentation Development Applied to Agriculture, of the Federal University of Lavras. There, under actual conditions of planting, a preliminary study was carried out with the green fruit stage, cherry and raisins, to ascertain the characteristics of shape, weight, size, color and especially the peel strength conditions of the peduncle. The values found in this analysis were the basis for the determination of operating parameters of the instrument for the main experiment. In the latter, case the vibrations, whose frequencies were measured through the apparatus, associated to the various positions where the grain is found in plants, have been adapted to a number of mechanical devices which, with the “LabVIEW” interface software, executed qualitatively and comparatively evaluated oscillations and comparatively in an experiential approach. This allowed the discovery of optimal values for the operating parameters of the harvesters and other equipment involved. Therefore, the vibrations of the experiment that provided the best conditions for the collection were the frequency from 38 to 88 Hz, which reduced efforts to harvest the fruits of better quality and enabled the analysis of the natural conditions of plant oscillation.